2018
DOI: 10.1097/md.0000000000013751
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of colorectal liver metastasis harboring intrahepatic cholangiocarcinoma

Abstract: Rationale:Colorectal liver metastasis develops in 50% of patients diagnosed with colorectal cancer, whereas concurrent intrahepatic cholangiocarcinoma (ICC) and colorectal liver metastases is extremely rare.Patient concerns:A 72-year-old man was referred to our hospital complaining of abdominal discomfort, diarrhea, and weakness over the last month.Diagnoses:Colorectal liver metastases concurrent intrahepatic cholangiocarcinoma (ICC).Interventions:The patient was treated with mFOLFOX6 (5-fluorouracil 2400 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…A controlled clinical trial reported longer PFS times in the bevacizumab combination group (6.48 months) than in the GEMOX group (3.72 months) [25]. There are cases of ICCs being successfully treated with bevacizumab combined with oxaliplatin-based chemotherapies as a consequence of misdiagnosed colorectal carcinoma liver metastasis [26,27]. Evidence supporting neoadjuvant or conversional treatment in ICC is lacking, but our results showed that late staged patients accepted combination of chemotherapy and bevacizumab treatment and consecutive operation had a longer PFS time than those underwent radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A controlled clinical trial reported longer PFS times in the bevacizumab combination group (6.48 months) than in the GEMOX group (3.72 months) [25]. There are cases of ICCs being successfully treated with bevacizumab combined with oxaliplatin-based chemotherapies as a consequence of misdiagnosed colorectal carcinoma liver metastasis [26,27]. Evidence supporting neoadjuvant or conversional treatment in ICC is lacking, but our results showed that late staged patients accepted combination of chemotherapy and bevacizumab treatment and consecutive operation had a longer PFS time than those underwent radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A review including several RCT has supported the effectiveness and similar oncologic outcomes of MI colectomy compared with open surgery in the setting of isolated colon cancer [96]. As of lymphadenectomy, revision of four casematched studies comparing MI and open approach including a total of 75 matched patients, showed no significant differences regarding adequacy of lymphadenectomy (including harvested lymph nodes) between the two approaches [29,36,61,97].…”
Section: Grade Of Recommendation Bmentioning
confidence: 99%
“…The review emphasized the significance of MDTs in developing tailored treatment plans and optimizing patient management, stressing the importance of a collaborative and comprehensive approach to address the complexities of CRLM[ 45 ]. Moreover, Cheng et al [ 46 ] highlighted the importance of a multidisciplinary treatment plan in achieving successful resection of colorectal liver metastases and intrahepatic cholangiocarcinoma, further emphasizing the role of MDTs in guiding complex treatment decisions[ 46 ].…”
Section: The Crucial Role Of Mdt In Customizing Individualized Approa...mentioning
confidence: 99%